2008
DOI: 10.3748/wjg.14.6704
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and histopathological evaluation of acute gastric injury in high-dose acetaminophen and nonsteroidal anti-inflammatory drug ingestion with suicidal intent

Abstract: AIM:To evaluate endoscopic and histopathologic aspects of acute gastric injury due to ingestion of high-dose acetaminophen and nonsteroidal antiinflammatory drugs (NSAIDs) with respect to some risk factors and patient characteristics. METHODS:The study group consists of 50 patients admitted to emergency department with high dose analgesic ingestion (group Ⅰ) with suicidal intent. Thirty patients with or without mild complaints of dyspepsia (group Ⅱ) were selected as the control group. The study group was strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…The results showed the highest level of epithelial erosion on (K+). These results are quite similar to the statement of Soylu et al (2008), that indomethacin inhibits the activity of the enzyme COX-1. Inhibition of COX-1 by indomethacin will reduce prostaglandin formation of gastric mucosa.…”
Section: Epithelial Erosionsupporting
confidence: 81%
“…The results showed the highest level of epithelial erosion on (K+). These results are quite similar to the statement of Soylu et al (2008), that indomethacin inhibits the activity of the enzyme COX-1. Inhibition of COX-1 by indomethacin will reduce prostaglandin formation of gastric mucosa.…”
Section: Epithelial Erosionsupporting
confidence: 81%
“…There was strong correlation between the age and the incidence of ulcer in patients receiving Ibuprofen as reported by Soylu A et al& Hernandez D [15][16]. But, our results provided that the incidence of ulcer not correlated to the age.…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast, Yuan YH et al concluded after reviewing randomized placebocontrolled trials of oral NSAIDs from 1975 to 2006, that the incidence of gastrodudenal ulcer in placebo arms has not changed significantly over the last three decades [14]. Similarly, Soylu A et al reported the absence of that statistically significant difference [15].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Those patients were not included in our study since it is not known if a history of GI ulcerations and bleeding increases the risk of acute stress-induced bleeding [8,9] . Similarly, NSAIDs were not thoroughly studied as risk factors for stress ulcers although their longterm use was associated with GI bleeding problems [37][38][39] ; (5) Current GI bleeding: Patients with active GI bleeding were also excluded from the study since those patients will be receiving AST as a pharmacologic intervention for the management of upper GI bleeding. Moreover, prophylaxis has no role and is not indicated in this population [40][41][42] ; (6) Lab tests including complete blood count, liver function tests and stool exam were documented to monitor for bleeding [43][44][45] ; (7) Stress ulcers risk factors: A stress ulcer risk stratification, adopted from the ASHP guidelines, divided patients into three categories: non-critically ill medical patients, ICU populations and pediatrics.…”
Section: Data Collectionmentioning
confidence: 99%